William Morris’s Conditional Moment - Ward, Megan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis article argues that William Morris’s “The Defence of Guenevere” (1858) writes history through a singular unit of the time, the ephemeral moment. The moment is constructed through sensory experience, lodging historical narrative in the body and departing from mainstream Victorian progressive narratives. Morris constructs what I call an historiography of conditionality, an historical consciousness predicated on the immanent self-contradiction of memorializing any particular moment. In doing so, Morris anticipates what Walter Benjamin and others, following Karl Marx, theorized as historical materialism. My reading of “The Defence of Guenevere” departs from critics who have labeled Morris as escapist, nostalgic, or someone who uses the past to critique the present. Instead, Morris creates a poetic historical consciousness that weighs the cost of memorialization for the present day.